1996
DOI: 10.1111/j.1467-9450.1996.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

The empirical relationships between standardized measures of religiosity and personality/mental health

Abstract: The aim of this study was to investigate the relationships between standardized, factor-based measures of religiosity and personality/mental health. In a sample of 471 self-identified Christian subjects, 303 females and 168 males, 79 non-psychotic psychiatric in-patients and 392 non-patients, personal extrinsicness was partially positively correlated with the BCI Obsessive score. In multiple regression analyses some of the factor-based religious orientation indices related differently to the BCI Oral, Obsessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Many studies show that religion shapes social and political attitudes in ways that cannot be reduced to social class, educational attainment, or other sociological factors (Davis and Robinson 1996; DiMaggio et al 1996; Green et al 1996; Leege and Kellstedt 1993; Manza and Brooks 1997; Wald 1987). Religion is also noteworthy because of its association with mental health and overall life satisfaction (Coke 1992; Glenn 1997; Ho et al 1995; Kaldestad 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show that religion shapes social and political attitudes in ways that cannot be reduced to social class, educational attainment, or other sociological factors (Davis and Robinson 1996; DiMaggio et al 1996; Green et al 1996; Leege and Kellstedt 1993; Manza and Brooks 1997; Wald 1987). Religion is also noteworthy because of its association with mental health and overall life satisfaction (Coke 1992; Glenn 1997; Ho et al 1995; Kaldestad 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, religious attendance has also been associated with greater life satisfaction (Kaldestad, 1996), lower incidence of depression (Jensen et al , 1993), and beneficial personal relationships through increased social contacts (Bradley, 1995). The growing literature surrounding the impact of religiosity, spirituality, and religious commitment has evolved to include a broad spectrum of health indices: mental health; physical health; and social health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis that there was a reciprocal interaction between religiosity and health, a stepwise multiple correlation analysis was conducted rather than the more customary multiple regression analysis. By interaction, it is meant that previous studies suggested that health status has an effect on religiosity and religiosity has an effect on health status (1,2,4,5,6). Thus, a more general multiple correlation analysis was applied.…”
Section: Discussionmentioning
confidence: 99%
“…There is systematic and quantitative evidence that religious commitment and religious practice are associated with better physical and mental health. Religious devotion has been linked to greater life satisfaction and improved psychological health (1,2,3), to lower incidence of depression (4,5), and to lower incidence of psychiatric disorders in general (6). Levin and Vanderpool reviewed scores of studies that found an association between the frequency of church attendance and physical health, although they urged that caution should be taken when interpreting such associations (7).…”
Section: Introductionmentioning
confidence: 99%